2020
DOI: 10.1016/j.electstud.2020.102118
|View full text |Cite
|
Sign up to set email alerts
|

The more the better? Cumulative issue ownership and intra-campaign party switching

Abstract: We contribute to the literature on short term changes in voters' party preferences (or intra-campaign party switching), by advancing a factor that has been neglected so far: Voters' perceptions about parties' issue competence. We develop a model of party switching that includes both classic predictors and issue ownership considerations. Moreover, in contrast to the usual single issue ownership conception focusing on the party deemed most competent to solve the most important problem, we argue that voters base … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…On the other hand, our results add to the issue ownership approach by pointing to how it can contribute to the explanation of party choice between ideologically close parties. Previous studies have demonstrated the importance of the short‐tern stability and change of issue ownership evaluations for the stability and change of voting behaviour for parties from different party camps (Lutz & Sciarini, 2016; Lanz & Sciarini, 2016; Petitpas & Sciarini, 2018, 2020). Our findings go one step further by showing that the issue ownership approach is also well‐suited to account for the choice between parties belonging to the same party bloc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, our results add to the issue ownership approach by pointing to how it can contribute to the explanation of party choice between ideologically close parties. Previous studies have demonstrated the importance of the short‐tern stability and change of issue ownership evaluations for the stability and change of voting behaviour for parties from different party camps (Lutz & Sciarini, 2016; Lanz & Sciarini, 2016; Petitpas & Sciarini, 2018, 2020). Our findings go one step further by showing that the issue ownership approach is also well‐suited to account for the choice between parties belonging to the same party bloc.…”
Section: Discussionmentioning
confidence: 99%
“…As recent studies show, citizens' perceptions of parties' issue competence change during electoral campaigns, which then has a significant influence on electoral choice formation (e.g. Lanz & Sciarini, 2016; Lutz & Sciarini, 2016; Petitpas & Sciarini, 2018, 2020).…”
Section: Voting For the Social Democrats Or The Greens: A Considerati...mentioning
confidence: 99%
“…The more popular variant of issue ownership voting concentrates on the “competence” dimension and shows that voters’ assessment of parties’ ability to handle important issues and to resolve problems of concern to voters influence their vote (e.g., Bélanger & Meguid, 2008; Green & Hobolt, 2008; Lanz, 2020). Moreover, it has been demonstrated that changing competence ownership perceptions are a predictor of party switching (Lanz & Sciarini, 2016; Petitpas & Sciarini, 2018) and that being considered most competent on several issues (that is, having “cumulative” issue ownership) has a greater effect on vote choice than owning only one salient issue (Karlsen & Aardal, 2016; Petitpas & Sciarini, 2020).…”
Section: Theoretical Framementioning
confidence: 99%
“…As recent studies confirm (Seeberg, 2017), issue ownership certainly has a highly stable long-term component-over time, the same party tends to be considered more competent to handle an issue by the voters. However, this does not mean that issue ownership cannot fluctuate in the short run (and even the longer run) and, at times, temporarily change hands (Egan, 2013;Petitpas and Sciarini, 2020;Stubager, 2018;Walgrave et al, 2009). Even if just temporary, such deviations from the long-term pattern may as demonstrated in case studies (see, e.g.…”
Section: Undermining a Rival Party's Issue Ownershipmentioning
confidence: 99%